Establishment and validation of a nomogram for predicting survival in patients with de novo metastatic nasopharyngeal carcinoma. (July 2019) - Sun, Xue-Song; Liang, Yu-Jing; Liu, Sai-Lan; Li, Xiao-Yun; Chen, Qiu-Yan; Guo, Shan-Shan; Wen, Yue-Feng; Liu, Li-Ting; Xie, Hao-Jun; Tang, Qing-Nan; Yan, Jin-Jie; Guo, Ling; et al.
Highlights: 502 de novo NPC patients were involved in the study. Five independent prognostic factors were entered into the nomogram. The C-index of the nomogram was 0.724 in primary cohort. A calibration curve was used to compare predicted and observed survival. All results were confirmed in the validation cohort. Abstract: Background and purpose: No nomogram has been established for de novo metastatic NPC patients previously. Thus, we retrospectively involved 502 de novo NPC patients to develop a practical clinical tool by combining prognostic biomarkers to estimate individual risk. Methods: The nomogram was based on a primary cohort involving 353 patients from 2007 to 2013; all independent prognostic factors were integrated for inclusion in the model. The predictive accuracy of the model was evaluated by concordance index (C-index). A calibration curve was used to compare predicted and observed survival. We confirmed the results using a validation cohort study on 149 patients enrolled from 2014 to 2016. Results: Five independent prognostic factors derived from multivariable analysis were entered into the nomogram. The C-index of the nomogram was 0.724. The calibration curves for probability of 3- and 5-year overall survival (OS) showed satisfactory agreement between predicted survival and actual observed survival. The Kaplan–Meier survival curves showed a significant difference in survival among different risk groups according to the total score. All results were confirmed in the validation cohort. Conclusion: We established a convenient nomogram that provides individual prediction of OS for patients with de novo metastatic NPC.